Evaluasi Proses Bisnis Layanan Bidang Pembinaan Pendidik Dan Tenaga Kependidikan (PTK) Di Dinas Pendidikan Kota Malang Menggunakan Metode Quality Evaluation Framework (QEF) - Nur Fatimah; Nanang Yudi Setiawan; Niken Hendrakusma Wardani (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Dinas Pendidikan Kota Malang is a government agency responsible for the education sector in Malang City and has several fields. One of them is the division of Pembinaan Pendidik dan Tenaga Kependidikan (PTK). In carrying out its business processes there were several problems that cause the quality of services provided to clients was not good, due to repeated activities, activities that require a long time and input processes that ware not in accordance with the requirements. Therefore a business process evaluation was needed using the Quality Evaluation Framework (QEF) method which was modeled using IDEF0 to model the functional process and IDEF3 to model the current sequence of business processes. The entire evaluation of business processes produced 6 quality factors that were not in accordance with the targets determined by stakeholders. This indicated a gap between targets and ongoing performance. The results of evaluating the quality factor mismatch will find the root of the problems using fishbone analysis. It can be concluded that the emergence of discrepancies was caused by repeated activities and input processes that were not in accordance with the provisions.